2022
DOI: 10.1029/2022jg006819
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Enrichment Increased Community Stability by Increasing Asynchrony and Dominant Species Stability in Alpine Meadow of Qinghai‐Tibet Plateau

Abstract: Song et al., 2019). Moreover, most studies on the ecosystem response to P increasing have focused on tropical, ancient, or highly biodiversity areas. The effects of P enrichment on ecosystem stability in cold and high-altitude ecosystems are less known (Soons et al., 2017).Nitrogen is closely related to plant metabolism and growth (Mitra, 2015). N deficiency will weaken plant photosynthesis, while N sufficiency will promote rapid plant growth (Wang et al., 2017;Yue et al., 2020). It is widely recognized that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 89 publications
2
13
0
Order By: Relevance
“…The rates of nitrogen and phosphorus addition and the duration of the study period in our research are comparable to many previously reported nutrient addition experiments that primarily focused on the responses of aboveground stability (e.g., Hautier et al, 2014Hautier et al, , 2015Wang, Jiang, et al, 2022;Yang et al, 2012;Zhang et al, 2016). However, our findings demonstrate that the aboveground and belowground stability had asymmetric responses, indicating that the prevalently investigated aboveground S6.…”
Section: Asymmetric Responses Of Aboveground and Belowground Stabilit...supporting
confidence: 85%
See 4 more Smart Citations
“…The rates of nitrogen and phosphorus addition and the duration of the study period in our research are comparable to many previously reported nutrient addition experiments that primarily focused on the responses of aboveground stability (e.g., Hautier et al, 2014Hautier et al, , 2015Wang, Jiang, et al, 2022;Yang et al, 2012;Zhang et al, 2016). However, our findings demonstrate that the aboveground and belowground stability had asymmetric responses, indicating that the prevalently investigated aboveground S6.…”
Section: Asymmetric Responses Of Aboveground and Belowground Stabilit...supporting
confidence: 85%
“…These findings remained unchanged when using the 4-year paired measurements of ANPP and BNPP (Appendix S1). These results indicate that the decrease in belowground stability can lead to a decline in the stability of TNPP, highlighting the whole ecosystem-scale consequences that were previously unknown due to the predominant focus on the aboveground stability (e.g., Wang, Jiang, et al, 2022;Yang et al, 2012). These findings also indicate that investigations solely focused on the aboveground stability are insufficient to reflect the ecological consequences of enriched nutrients.…”
Section: Asymmetric Responses Of Aboveground and Belowground Stabilit...mentioning
confidence: 80%
See 3 more Smart Citations